An effective powerful test for one-sided supplier selection problem with multiple independent characteristics. Issue 2 (2nd April 2016) - Pearn, W. L.; Wu, Chia-Huang; Chuang, Ching-Ching
Abstract: In this paper, we use the index to investigate the supplier selection problem for one-sided processes with multiple independent characteristics. We first review the existing approach, which we refer to as the division method, then develop a new exact approach called the subtraction method. A two-stage selection procedure is developed based on the subtraction method for practical applications. We then compared the two methods with regard to selection power. The results show that the subtraction method we propose is indeed more powerful than the existing division method. A thin-film transistor type liquid-crystal display (TFT-LCD) application example is provided to illustrate the testing procedure.